2017
DOI: 10.9788/tp2017.4-19
|View full text |Cite
|
Sign up to set email alerts
|

The Family Environment Assessment: Study of the Use of the EC-HOME in a Brazilian Sample

Abstract: The family environment may impact child development. However, investigating the family environment in Brazil can be a challenge due to the lack of appropriate instruments. To systematize the study of family environment the Home Observation for Measurement of the Environment Inventory (HOME) was developed. The executive functions (EF), important for the control of thinking, behavior and emotion are among the skills affected by variables of the family environment. This study investigated reliability and validity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
0
5
1
Order By: Relevance
“…When comparing the home environment score with that of other countries, the present research's environment scores were lower than those found in a Korean study for almost all EC-HOME subscales [10]. Moreover, the home environment scores analyzed in a Brazilian study were lower than those in this study in almost all EC-HOME aspects [11]. This point shows that the difference in context, culture and parenting in each country affects the home environment scores and child development.…”
Section: Discussioncontrasting
confidence: 89%
“…When comparing the home environment score with that of other countries, the present research's environment scores were lower than those found in a Korean study for almost all EC-HOME subscales [10]. Moreover, the home environment scores analyzed in a Brazilian study were lower than those in this study in almost all EC-HOME aspects [11]. This point shows that the difference in context, culture and parenting in each country affects the home environment scores and child development.…”
Section: Discussioncontrasting
confidence: 89%
“…Of note, although previous international groups from different countries, including Brazil, used the Home Observation for Measurement of the Environment - HOME Inventory, the instrument has not been subject to an analysis of measurement equivalence/invariance cross-culturally [ 55 ]. However, we noteworthy that the HOME Inventory has been used worldwide to evaluate the home environment in both international [ 54 ] and transcultural studies [ 55 ], presenting psychometric characteristics that were investigated in Brazilian preschoolers sample [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…For the elaboration of the multicriteria index of physical environmental opportunities, we used two items of the subscale III of the referred instrument, which assesses, among others, the presence of a yard and the internal physical environment of the house considering 30m 2 per inhabitant. The HOME Inventory has been used worldwide to evaluate the home environment in both international [ 54 ] and transcultural studies [ 55 ], presenting psychometric characteristics investigated in Brazilian preschoolers sample- analysis of internal consistency satisfactory for the total scale (Cronbach’s Alpha = .84 for the 55 items) [ 56 ].…”
Section: Methodsmentioning
confidence: 99%
“…The sum of the raw scores of the subscales was used for analyses. The HOME Inventory has been used worldwide to evaluate the home environment in both international [ 38 ] and transcultural studies [ 39 ], presenting psychometric characteristics investigated in Brazilian preschoolers (Cronbach’s Alpha = .84 for the 55 items) [ 40 ].…”
Section: Methodsmentioning
confidence: 99%